2018
DOI: 10.3390/molecules23051061
|View full text |Cite
|
Sign up to set email alerts
|

Essential Oils and Their Constituents Targeting the GABAergic System and Sodium Channels as Treatment of Neurological Diseases

Abstract: Essential oils and the constituents in them exhibit different pharmacological activities, such as antinociceptive, anxiolytic-like, and anticonvulsant effects. They are widely applied as a complementary therapy for people with anxiety, insomnia, convulsion, pain, and cognitive deficit symptoms through inhalation, oral administration, and aromatherapy. Recent studies show that essential oils are emerging as a promising source for modulation of the GABAergic system and sodium ion channels. This review summarizes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
52
1
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 80 publications
(57 citation statements)
references
References 114 publications
(208 reference statements)
0
52
1
4
Order By: Relevance
“…The impacts of exposure to essential oils can be classified into psychological impacts and physiological impacts. The psychological impacts found in non-human animals, mostly using mice or rats, are anxiolytic effects, suppression of depression, anti-agitation, as a relaxant, and anti-stress effects [91], which may all be related to a relaxing effect through suppression of anxiety, stress, agitation, and depression. Some studies suggest that English lavender (Lavendula angustifolia) has the strongest anxiolytic effect [92].…”
Section: Psychological and Physiological Impact Of Essential Oilsmentioning
confidence: 99%
See 4 more Smart Citations
“…The impacts of exposure to essential oils can be classified into psychological impacts and physiological impacts. The psychological impacts found in non-human animals, mostly using mice or rats, are anxiolytic effects, suppression of depression, anti-agitation, as a relaxant, and anti-stress effects [91], which may all be related to a relaxing effect through suppression of anxiety, stress, agitation, and depression. Some studies suggest that English lavender (Lavendula angustifolia) has the strongest anxiolytic effect [92].…”
Section: Psychological and Physiological Impact Of Essential Oilsmentioning
confidence: 99%
“…Some studies suggest that English lavender (Lavendula angustifolia) has the strongest anxiolytic effect [92]. The physiological impacts of essential oils are broader, i.e., improving wound healing, as an analgesic, an anti-nociceptive, an anti-fungal, an anti-inflammatory, an anti-oxidant, a local anesthesia, a sedative, an anesthetic systemic, having anti-convulsant effects, and others [91,92] ( Table 2). Studies using human subjects have found differences in effectiveness, depending on the essential oils as shown above.…”
Section: Psychological and Physiological Impact Of Essential Oilsmentioning
confidence: 99%
See 3 more Smart Citations